Effect of hemoglobin extracted from Tegillarca granosa on iron deficiency anemia in mice. (December 2022) - Sun, Bolun; Zhang, Panxue; Wei, Huamao; Jia, Ru; Huang, Tao; Li, Chao; Yang, Wenge
Graphical abstract: Highlights: IDA-caused alterations of biochemical indicators were ameliorated after T. granosa hemoglobin supplementation. Oral administration of T. granosa hemoglobin was more effective in IDA treatment than ferrous sulfate. SF, sTfR and hepcidin appeared to be important indicators for IDA. In vivo experiment suggested that hemoglobin exhibited excellent therapeutic effects for IDA mice. Abstract: Iron deficiency anemia (IDA) is the most common nutritional deficiency in the world. This study was aimed to evaluate the therapeutic effects of hemoglobin from Tegillarca granosa ( T. granosa ) on IDA in mice. Mice were randomly divided into five groups: a normal control group, an anemia model group, a positive (FeSO4 ) control group, a low-dose and high-dose hemoglobin groups. After 4-week iron supplements administration, it was observed that hemoglobin at 2.0 mg iron/kg body weight had better restorative effective on IDA mice than that of FeSO4 with regard to routine blood parameters and serum biochemical indicators. Meanwhile, the IDA-caused alterations of organ coefficients and liver morphology were ameliorated in mice after hemoglobin supplementation in a dose-dependent manner. Further correlation analysis of indicators showed that serum ferritin (iron storage protein) and soluble transferrin receptor (cellular iron uptake membrane glycoprotein) were susceptible to iron deficiency, indicating possible disorder of iron metabolism caused by IDA. And levels of serum ferritin and soluble transferrin receptor were restored after administration of hemoglobin. These findings confirmed the safety and effectiveness of T. granosa derived hemoglobin in alleviating IDA in mice, suggesting its great potential as an alternative for iron supplementation.